Digitalization, Branding, and Network Collaboration Strategy among SMTEs: Preliminary Qualitative Analysis - Wardhani, Windi Novia Ratri; Purnomo, Purnomo; Pratiwi, Ratih; Nasution, Saipul (Journal of Digital Marketing and Halal Industry, 2023)
The primary objective of this research is to develop strategies enabling Small and Medium Tourism Enterprises (SMTEs) to effectively navigate and actively participate in digital transformation and collaborative networks. Employing a qualitative methodology with the application of Quantitative Strategic Planning Matrix (QSPM) analysis, data for this study is gathered through direct observations and interviews involving stakeholders in the tourism industry, local government, village authorities, and tourism business associations such as PHRI (Persatuan Hotel dan Restoran Indonesia) and BPW (Badan Pariwisata Wisatawan). The key findings underscore the significance of (1) fostering a positive service reputation culture, (2) involving diverse stakeholders in establishing a sustainable tourism destination management system, and (3) reinforcing tourism promotion efforts through the strategic use of expanded digital media channels. The practical implications of this research extend to providing tangible guidance for SMTEs to actively enhance their services for tourists. The distinctive contributions of this study manifest in three key dimensions. Firstly, the introduction of the service reputation culture as an innovative approach supports the evolution of novel services in the tourism industry. Secondly, it addresses the underexplored research theme of SMTEs, filling a significant knowledge gap. Thirdly, the utilization of QSPM analysis in this study showcases originality, as this analytical method is rarely employed in analogous contexts. Consequently, this research contributes unprecedented insights to the strategic understanding of SMTEs within the realm of service reputation culture, paving the way for innovative and informed approaches in the tourism industry.